Sosialisasi Anti Korupsi Dalam Mencegah Tindak Pidana Korupsi Bagi Para Pelajar di Kecamatan Kuta, Propinsi Bali - Sumartono, Agus (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2025)
Early anti-corruption education for students is essential to prevent potential acts of corruption, which can harm state finances. The socialization of anti-corruption behavior for students aims to raise awareness so that students know and understand anti-corruption behavior which is the root cause of the emergence of the seeds of corruption. The socialization of anti-corruption behavior was carried out in several schools in Kuta sub-district, Bali Province. It is hoped that this socialization can increase the understanding of students, educators, and the surrounding community about the importance of anti-corruption behavior that must be instilled from an early age, as well as educate them about preventive measures that can be taken to protect students and educators from committing corruption. In addition, this socialization also aims to increase cooperation between various parties, including government agencies, educational institutions, and the community, in tackling anti-corruption behavior in the community. The method of socialization of anti-corruption behavior in preventing corruption in Kuta District, Bali Province by conducting surveys, activities, and team evaluation. The stages of socialization of anti-corruption behavior are carried out by conducting surveys and problem identification, program planning, material development and activity preparation, activity implementation, documentation, and evaluation. It is expected that the implementation of this socialization will be useful for students in the Kuta sub-district area, this socialization is expected to help create an environment free from corrupt behavior, especially in the educational environment.